Mucinous ovarian cancer. Issue 2 (1st February 2008) - Harrison, M. L.; Jameson, C.; Gore, M. E.
Abstract : Mucinous epithelial ovarian cancer (mEOC) accounts for approximately 10% of EOCs. Patients presenting with early-stage disease have an excellent prognosis, however, those with advanced disease have a poor outcome with relative resistance to standard ovarian cancer chemotherapy. Molecular and genetic studies demonstrate differences between mucinous and serous EOC supporting the concept that these tumors develop along separate pathways. Together with the observed differences in clinical behavior and outcome for mEOC, there is a need to develop specific therapeutic strategies for this histologic subtype. The relative rarity of advanced mEOC has resulted in few patients enrolled in major ovarian cancer trials. The results of such trials may not necessarily reflect those specific to mEOC. Separate trials testing alternative chemotherapeutics are required. Metastatic mucinous tumors from other sites such as the gastrointestinal tract may present with ovarian involvement. For all mucinous tumors of the ovary, establishing primary as opposed to metastatic cancers is important. Clinical presentation, tumor markers, histologic, and immunohistochemical features are helpful in distinguishing most cases.